Ars Aevi Collection : Museum of Contemporary Art Sarajevo 1992-2002. - Hadziomerspahic, Enver (Sarajevo : ARS AEVI, 2002)
Abramovic, Marina ; Accardi, Carla ; Anur ; Apfelbaum, Polly ; Aslan, Nora ; Badiola, Txomin ; Bagnoli, Marco ; Bajevic, Maja ; Balka, Miroslav ; Balkenhol, Stephan ; Bassiri, Bizhan ; Beuys, Joseph ; Bianchi, Domenico ; Boetti, Alighiero ; Boltanski, Christian ; Bottinelli Montandon, Mario ; Brus, Günter ; Bul, Lee ; Buren, Daniel ; Cabrita Reis, Pedro ; Calle, Sophie ; Cannavacciuolo, Maurizio ; Cano, Eugenio ; Cardini, Marco ; Castellani, Enrico ; Ceric, Suzana ; Compagnucci, Andrés Gaston ; Cragg, Tony (Anthony) ; Dakic, Danica ; Deacon, Richard ; Dessi, Gianni ; Dibbets, Jan ; Dimitrijevic, Braco ; Drozdik, Orshi ; Friedmann, Gloria ; Frize, Bernard ; Gabriel, Sieglind ; Gechtman, Gideon ; Goldin, Nan ; Habicht, Dejan ; Hadzifejzovic, Jusuf ; Hafström, Jan ; Hajdu, Szabolcs ; Han Myung-Ok ; Hartley, Alex ; Hatoum, Mona ; Inspection "Medical Hermeneutics" ; IRWIN ; Jokanovic-Toumin, Dean ; Jürgenssen, Birgit ; Kabakov, Ilya ; Kajinic, Anto ; Kameric, Sejla ; Kapoor, Anish ; Kaufmann, Massimo ; Kempinger, Herwig ; Komar & Melamid ; Kopystianskaya, Svetlana ; Kosuth, Joseph ; Kounellis, Jannis ; Kowanz, Brigitte ; Kozaris, Dimitris ; Kushner, Robert ; Lavier, Bertrand ; Lazetic, Tanja ; Leupold-Löwenthal, Daniela ; Levini, Felice ; LeWitt, Sol ; Libovac, Fikret ; Liv, Lena ; Maggio, Elisabetta di ; Mattiacci, Eliseo ; Messina, Vittorio ; Mulasics, Laszlo ; Muñoz, Juan ; Muntean & Rosenblum ; Nagasawa, Hidetoshi
Italiaans & Bosnisch & Engels
Ars Aevi Collection, Ars Aevi Museum of Contemporary Art, Sarajevo, 23.06 - 25.06.2002
boek